Transformasi Pendidikan Pancasila dan Kewarganegaraan (PPKn) Melalui Integrasi Teknologi - Nurlaili, Lili; Utami, Sri (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
Education is the main and superior investment in a country’s civilization. Thus, education throughout the world always experiences different trens. According to the Ministry of Education and Culture 2020, there are 4 trens that need to be taken into account, one of which is technological progress. Pancasila and Citizenship education as one of the important subjects in schools is also experiencing changes in learning by using Artificial Intelligence (AI). The purpose of this article is that PPKn educators care more about technological developments that help them to achieve better learning, as well as understand the educational policies that are being implemented. The methods used are lecture, question and answer, and presentation methods. The findings are: Many teachers do not understand the integration of AI in Civics learning. Conclusion: There is still a need for activities that strengthen teachers to understand how to use artificial technology in Civics learning.